Octahedral molybdenum cluster complexes with aromatic sulfonate ligands. Issue 39 (7th September 2016) - Efremova, Olga A.; Vorotnikov, Yuri A.; Brylev, Konstantin A.; Vorotnikova, Natalya A.; Novozhilov, Igor N.; Kuratieva, Natalia V.; Edeleva, Mariya V.; Benoit, David M.; Kitamura, Noboru; Mironov, Yuri V.; Shestopalov, Michael A.; Sutherland, Andrew J.
Abstract : Synthesis, structure and systematic study of the redox and spectroscopic properties of [Mo6 X8 (aromatic sulfonate)6 ] 2− . Abstract : This article describes the synthesis, structures and systematic study of the spectroscopic and redox properties of a series of octahedral molybdenum metal cluster complexes with aromatic sulfonate ligands ( n Bu4 N)2 [Mo6 X8 (OTs)6 ] and ( n Bu4 N)2 [Mo6 X8 (PhSO3 )6 ] (where X − is Cl −, Br − or I − ; OTs − is p -toluenesulfonate and PhSO3 − is benzenesulfonate). All the complexes demonstrated photoluminescence in the red region and an ability to generate singlet oxygen. Notably, the highest quantum yields (>0.6) and narrowest emission bands were found for complexes with a Mo6 I8 4+ cluster core. Moreover, cyclic voltammetric studies revealed that ( n Bu4 N)2 [Mo6 X8 (OTs)6 ] and ( n Bu4 N)2 [Mo6 X8 (PhSO3 )6 ] confer enhanced stability towards electrochemical oxidation relative to corresponding starting complexes ( n Bu4 N)2 [Mo6 X8 X6 ].